Perancangan Motif Batik Salak Padangsidimpuan Dalam Kemeja - Maisari Purwaningsih; Ahmad Bahrudin; Taufik Akbar (Institut Seni Indonesia Padangpanjang, 2022)
Padangsidimpuan snakefruit is fruit come from a vilage named sibakkua and huta lambung tapanuli selatan. It has like skin snake with dark bourn skin. Salak padangsidimpuan bigger and then other’s. Padangsidimpuan snakefruit is an icon in padangsidimpuan and is interesting in making it a batik motive on a shirt. The beginning of the creation method will look for an idea and alternative design and the selected design pacing size and make pattern with skala and then process creating the art. The creation made three sections: in shirt batik with padangsidimpuan snakefruit as a motif, the creation name with martunas, sasumpit salak, and matapor.